KAJIAN BIBLIKA TERHADAP BERITA HOAX TEMPO DULU TERHADAP BAHAYA BERITA HOAX DALAM MEDIA SOSIAL MASA KINI - Johanes Witoro (Jurnal Teologi Biblika, 2020)
This research is intended to find a biblical study between past hoax news and the dangers of hoax news in today's social media. This study uses a qualitative writing method by using exsegesa study of the Bible as the basis of essential truth, supported by various sources related to the existing discussion topics. In the discussion, it turns out that there is a similarity between "fairy tales and myths" and human laws, which are contained in Surah Titus 1: 13-14 and 1Tim 4: 7, which are fake news made by a person to achieve certain goals, including damaging personal relationships with neighbor, but also destroy the faith and belief in God. In today's media it seems the same, that hoax is someone's trick or slander, lies that are packaged as if they are true, but the truth is lies. In this journal a solution has been found that, hoax news must be stopped because it is detrimental to others and there is no positive value that can be taken. First, hold true teaching that lying is a sin and harms others. Second, be selective in choosing the right news by looking for reliable sources.